Business Development of Cardamom In Karanglewas Village - Intan Shaferi; Rio Dhani Laksana; Alisa Tri Nawarini (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Business development with great potential is very important, especially during the Covid-19 period where many businesses were destroyed but some businesses had the opportunity to be developed. The business development strategy is carried out to deal with the difficulties experienced by partners so that it becomes a solution that can be implemented. Like the results of the cardamom spice plant in Karanglewas. The packaging and management of the product is not optimal, so it still does not provide maximum profit. Through attractive packaging and processing of products into ready-to-sell powder, it is hoped that cardamom will become easier to market and more widely known to the public.